Student loan as a form of financing - Cieślak, Daria (Journal of Finance and Financial Law, 2019)
In Poland, student loans have been granted since 1998. As it turns out, they are not quite popular nowadays and there are fewer and fewer student loans from year to year. The question arises why this is happening and what affects it? The purpose of this article is to present and evaluate the functioning of student loans and explain the situation why several thousand of them were granted a few years ago, but much less at present (2019). The relationship between a strong financial standing and the decision to take a student loan will also be presented.